Digital image correlation and finite element modelling as a method to determine mechanical properties of human soft tissue in vivo. - SIMMS, CIARAN; MOERMAN, KEVIN MATTHEUS (My University, 2009)
The mechanical properties of human soft tissue are crucial for impact biomechanics, rehabilitation engineering and surgical simulation. Validation of these constitutive models using human data remains challenging and often requires the use of non-invasive imaging and inverse finite element (FE) analysis. Post processing data from imaging methods such as tagged magnetic resonance imaging (MRI) can be challenging. Digital Image Correlation (DIC) however is a relatively straightforward imaging method and thus the goal of this study was to assess the use of DIC in combination with FE modelling to determine the bulk material properties of human soft tissue. Indentation experiments were performed on a silicone gel soft tissue phantom. A two camera DIC setup was then used to record the 3D surface deformation. The experiment was then simulated using a FE model. The gel was modelled as Neo-Hookean hyperelastic and the material parameters were determined by minimising the error between the experimental and FE data. The iterative FE analysis determined material parameters (?=1.80 kPa, ?=2999 kPa) which were in close agreement with parameters derived independently from regression to uniaxial compression tests (? =1.71 kPa, ?=2857 kPa). Furthermore the FE model was capable of reproducing the experimental indentor force as well as the surface deformation found (R2=0.81). It was therefore concluded that a two camera DIC configuration combined with FE modelling can be used to determine the mechanical properties of materials that can be represented using hyperelastic Neo-Hookean constitutive laws.
PUBLISHED
PMID: 19362312
Keywords: Bioengineering; Digital image correlation; Iterative finite element modelling; Smart & Sustainable Planet